Brown v. Board of Education : a fight for simple justice - Rubin, Susan Goldman (Holiday House, 2016)
Chronicles the personal and political stories behind the "Brown v. Board of Education" Supreme Court case that ended school segregation. Discusses the work of the NAACP, the Supreme Court judges, children affected by the ruling, and persisting issues with diversity and segregation in schools today. Includes text of the Fourteenth Amendment and the Brown v. Board case as well as an index.